The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/cbdv.201600286
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Essential Oil Compositions of Lavandula pubescens (Lamiaceae) Aerial Parts Growing Wild in Yemen

Abstract: Lavandula pubescens Decne. is one of five Lavandula species growing wild in Yemen. The plant is used in Yemeni traditional medicine, and the essential oil tends to be rich in carvacrol. In this work, L. pubescens was collected from eight different locations in Yemen, the essential oils obtained by hydrodistillation, and the oils analyzed by gas chromatography/mass spectrometry (GC/MS). Principal component analysis (PCA) and hierarchical cluster analysis (HCA) were used to differentiate between the L. pubescens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
3
8
0
1
Order By: Relevance
“…Sesquiterpene hydrocarbons accounted for 13.1%, with β-bisabolene as the most abundant (9.1%). The predominance of carvacrol and methyl carvacrol as the most abundant compounds in the L. pubescens EO of this study is in accordance with published compositions of the EOs hydrodistilled from several Yemeni specimens [ 29 , 30 ]. This species is, indeed, reported as having a phenolic-type EO profile among species belonging to this genus [ 39 ].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Sesquiterpene hydrocarbons accounted for 13.1%, with β-bisabolene as the most abundant (9.1%). The predominance of carvacrol and methyl carvacrol as the most abundant compounds in the L. pubescens EO of this study is in accordance with published compositions of the EOs hydrodistilled from several Yemeni specimens [ 29 , 30 ]. This species is, indeed, reported as having a phenolic-type EO profile among species belonging to this genus [ 39 ].…”
Section: Resultssupporting
confidence: 91%
“…L. pubescens is reported in the literature as a species commonly found among the wild flora in Middle-Eastern Asia and Mediterranean Africa; it is, indeed, mainly reported as growing in Palestine [ 28 ], Yemen [ 29 , 30 , 31 ], Saudi Arabia [ 32 , 33 , 34 ]. For P. incisa subsp.…”
Section: Introductionmentioning
confidence: 99%
“…e oxygenated monoterpenes were the dominant (73.26%) chemical group within the constituents, followed by sesquiterpene hydrocarbons (13.84%), monoterpene hydrocarbons (11.79%), and oxygenated sesquiterpenes (1.11%). e EO chemical profile in this study is qualitatively comparable to that formerly reported from Yemen where the EO has shown to be carvacrol chemotype (60.9-77.5%) [6,31].…”
Section: Gc-ms Analysissupporting
confidence: 87%
“…ere are no reports on the EO composition of L. pubescens growing wild in Palestine and only a few such reports are available worldwide [6,8,13,31]. Hydrodistillation of the L. pubescens leaves yielded 1.9 mL per 250 g fresh plant material.…”
Section: Gc-ms Analysismentioning
confidence: 99%
“…Another two endemic species are L. pinnata and L. pubescens collected in Spain and Yemen, were studied by Argentieri et al . and Al Badani et al . Both were carvacrol chemotypes with a variable amount of carvacrol methyl ether and caryophyllene oxide as other main compounds.…”
Section: Essential Oils: Very Old ‘Guys’ With Great Prospectsmentioning
confidence: 99%